PREPARATION, CHARACTERIZATION, AND TOXICITY STUDY OF ANDROGRAPHIS PANICULATA ETHANOL EXTRACT POLY-LACTIC-CO-GLYCOLIC ACID (PLGA) NANOPARTICLES IN RAW 264.7 CELLS - KURNIAWAN, DHADHANG WAHYU; AINI GUMILAS, NUR SIGNA; ARRAMEL; HARTATI; NOVRIAL, DODY; TARWADI (International Journal of Applied Pharmaceutics, 2024)
Objective: This research aims to prepare and characterize Andrographis paniculata ethanol extract nanoparticles using Poly-Lactic-co-Glycolic Acid (PLGA) and test the toxicity of the nanoparticles in vitro in Raw 264.7 macrophage cells. Methods: A. paniculata ethanol extract-PLGA nanoparticles were prepared using the solvent evaporation method. The nanoparticles were characterized for their particle size and particle size distribution using a Particle Size Analyzer (PSA) and their zeta potential was measured using a zetasizer. The morphology of the nanoparticles was observed using a Scanning Electron Microscope (SEM). To confirm whether the ethanol extract of A. paniculata was loaded in the PLGA nanoparticles, it was determined using Fourier Transform Infra-Red (FTIR) and Raman spectroscopy. In vitro toxicity test of A. paniculata ethanol extract nanoparticles in Raw cells macrophage 264.7 using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. Results: After measurements using PSA, A. paniculata ethanol extract nanoparticles had an average size of 466.4 ± 31.6 nm, a Polydispersity Index (PdI) of 0.365 ± 0.03, and a zeta potential of-2.42 ± 0.91 mV. The results of observations using FTIR on A. paniculata ethanol extract nanoparticles show peaks at wavenumbers 712 cm-1, 749 cm-1, 865 cm-1, 955 cm-1, 1093 cm-1, 2949 cm-1, 1757 cm-1, and 3390 cm-1. This proves that A. paniculata ethanol extract is loaded into the nanoparticles. The results of in vitro toxicity tests using Raw macrophage 264.7 cells showed that the ethanol extract of A. paniculata-PLGA nanoparticles was not toxic. Conclusion: PLGA-based A. paniculata ethanol extract nanoparticles have good characteristics as a nanotechnology-based preparation and are non-toxic when tested in vitro in Raw macrophage cells 264.7.